Hyperglycemia reduces functional expression of astrocytic Kir4.1 channels and glial glutamate uptake. (3rd December 2015) - Rivera-Aponte, D.E.; Méndez-González, M.P.; Rivera-Pagán, A.F.; Kucheryavykh, Y.V.; Kucheryavykh, L.Y.; Skatchkov, S.N.; Eaton, M.J.
Highlights: The effect of hyperglycemia on astrocytic potassium channel function was studied. Hyperglycemia decreases astrocytic Kir4.1 mRNA and protein levels. Hyperglycemia impairs K + buffering and glutamate clearance by astrocytes. Abstract: Diabetics are at risk for a number of serious health complications including an increased incidence of epilepsy and poorer recovery after ischemic stroke. Astrocytes play a critical role in protecting neurons by maintaining extracellular homeostasis and preventing neurotoxicity through glutamate uptake and potassium buffering. These functions are aided by the presence of potassium channels, such as Kir4.1 inwardly rectifying potassium channels, in the membranes of astrocytic glial cells. The purpose of the present study was to determine if hyperglycemia alters Kir4.1 potassium channel expression and homeostatic functions of astrocytes. We used q-PCR, Western blot, patch-clamp electrophysiology studying voltage and potassium step responses and a colorimetric glutamate clearance assay to assess Kir4.1 channel levels and homeostatic functions of rat astrocytes grown in normal and high glucose conditions. We found that astrocytes grown in high glucose (25 mM) had an approximately 50% reduction in Kir4.1 mRNA and protein expression as compared with those grown in normal glucose (5 mM). These reductions occurred within 4–7 days of exposure to hyperglycemia, whereas reversal occurred between 7 and 14 days after return to normal glucose. The decrease in functional Kir channels in the astrocytic membrane was confirmed using barium to block Kir channels. In the presence of 100-μM barium, the currents recorded from astrocytes in response to voltage steps were reduced by 45%. Furthermore, inward currents induced by stepping extracellular [K + ]o from 3 to 10 mM (reflecting potassium uptake) were 50% reduced in astrocytes grown in high glucose. In addition, glutamate clearance by astrocytes grown in high glucose was significantly impaired. Taken together, our results suggest that down-regulation of astrocytic Kir4.1 channels by elevated glucose may contribute to the underlying pathophysiology of diabetes-induced CNS disorders and contribute to the poor prognosis after stroke.